STUDI PERBANDINGAN FENOMENA GO-JEK TERHADAP KEMAMPUAN NEGARA DALAM MENYEDIAKAN PELAYANAN TRANSPORTASI PUBLIK BERKUALITAS. - Sofyan Dwi Fari; Teguh Yuwono; Dzunuwanus Ghulam Manar (Journal of Politic and Government Studies, 2016)
This research is motivated by the presence of Transportation GO-jack in Semarang City. GO-Jek presence became an own interest for people in the Semarang City. In addition to the convenience provided by the Go-Jek is also a transportation alternative that is easily accessed by the public phenomenon of Go-Jek has become a stumbling block to the government in carrying out public transportation in the Semarang City. This is because the public already saturated transport exist today. The method used in this study is a research method combined with qualitative and quantitative approach with descriptive methods. The purpose of this study is to obtain data about the community and the government's response assessment will be the phenomenon of Go-Jek be an inability of the state to provide quality transportation services. These results indicate the characteristics of the choice of using Go-Jek for being able to provide accessibility for an easier, more flexible, more personalized and performance services better, more orderly would traffic signs, conditions and facilities of vehicles that are viewed and comfortable, high availability and better reliability.